STRATEGI PUBLIC RELATIONS PT. TELKOM WITEL BALI SELATAN DALAM MEMBANGUN BRANDIMAGE MELALUI PROMO PRODUK - Cipta Dewi, Ni Nyoman (Jurnal Kajian Ilmu Komunikasi, 2021)
Communication is done to promote the product must be of a quality to the product being offered is increasing. Public relations strategy is one that can dihandal communication in marketing and promoting the product. Of these problems, the researchers raised the title "Strategic Public Relations PT. Telkom South Bali Witel In Building Brand Image Through Promo Products". Problems were obtained, namely how the application of public relations strategy to build brand image ?. This study aims to determine the application of public relations strategy PT. Telkom South Bali Witel in building brand image. Based on the analysis of public relations strategy PT. Telkom South Bali Witel in building brand image through promo products have several ways communicator public relations strategies, goals and strategies in determining the strategy of using media and promotional channels. By choosing and placing the appropriate words and language so that the message would be delivered understood by the public. In building the brand image through the promotion of products, companies must improve the way of communication so that people can understand what the use of the products released